(untitled) (AMJ (Advanced Medical Journal), 2023)
Background and objectives: Reduced fetal movement is a reason for concern in both mothers and clinicians. The objective of this study was to assess the pregnancy characteristics and perinatal outcomes in women with decreased fetal movements. Methods: A case-control study was conducted on 489 pregnant women in Maternity Teaching Hospital, Erbil city from October 2021 to December 2022. They were assigned into two groups, cases consisting of 244 women with a perception of reduced fetal movements and a control group including 245 women with good fetal movements. perinatal outcome was compared between the two groups. Results: The majority (59.5%) of the study participants were term pregnancies (? 37weeks). Among women with RFM, 32.4% were nulliparous and 59% were multiparous comparing to control group (26.9% and 63.7%, respectively). A higher proportion of women with reduced fetal movements had gestational diabetes (34%), and preeclampsia (40.2%), compared to women of Group II with the rate of 15.5% and 21.2% respectively. The rate of cesarean section was significantly higher among cases than controls (45% vs. 24.9%, respectively). The rate of abnormal Doppler among Group I women was higher than in Group II women (26.2% versus 2.9%). Significantly higher rate of neonates in Group I had low APGAR score. Conclusions: Perception of reduced fetal movements is a reason for woman to contact their healthcare providers. The poor perinatal outcome is more evident in women with reduced fetal movements.